Mucins Suppress Virulence Traits of Candida albicans - Nicole L. Kavanaugh (American Society for Microbiology, 2014)
ABSTRACT Candida albicans is the most prevalent fungal pathogen of humans, causing a variety of diseases ranging from superficial mucosal infections to deep-seated systemic invasions. Mucus, the gel that coats all wet epithelial surfaces, accommodates C. albicans as part of the normal microbiota, where C. albicans resides asymptomatically in healthy humans. Through a series of in vitro experiments combined with gene expression analysis, we show that mucin biopolymers, the main gel-forming constituents of mucus, induce a new oval-shaped morphology in C. albicans in which a range of genes related to adhesion, filamentation, and biofilm formation are downregulated. We also show that corresponding traits are suppressed, rendering C. albicans impaired in forming biofilms on a range of different synthetic surfaces and human epithelial cells. Our data suggest that mucins can manipulate C. albicans physiology, and we hypothesize that they are key environmental signals for retaining C. albicans in the host-compatible, commensal state. IMPORTANCE The yeast Candida albicans causes both superficial infections of the mucosa and life-threatening infections upon entering the bloodstream. However, C. albicans is not always harmful and can exist as part of the normal microbiota without causing disease. Internal body surfaces that are susceptible to infection by C. albicans are coated with mucus, which we hypothesize plays an important role in preventing infections. Here, we show that the main components of mucus, mucin glycoproteins, suppress virulence attributes of C. albicans at the levels of gene expression and the corresponding morphological traits. Specifically, mucins suppress attachment to plastic surfaces and human cells, the transition to cell-penetrating hyphae, and the formation of biofilms (drug-resistant microbial communities). Additionally, exposure to mucins induces an elongated morphology that physically resembles the mating-competent opaque state but is phenotypically distinct. We suggest that mucins are potent antivirulence molecules that have therapeutic potential for suppressing C. albicans infections.